Capsicum chinense MYB Transcription Factor Genes: Identification, Expression Analysis, and Their Conservation and Diversification With Other Solanaceae Genomes - Islam, Khushbu; Rawoof, Abdul; Ahmad, Ilyas; Dubey, Meenakshi; Momo, John; Ramchiary, Nirala (Frontiers in Plant Science, 2021)
MYB genes are important transcriptional regulators of plant growth, development and secondary metabolic pathways, including capsaicinoid biosynthesis in Capsicum. Although MYB genes have been identified in Capsicum annuum, no comprehensive study has been conducted in other Capsicum species. We identified a total of 251 and 240 MYB encoding genes in C. chinense (CcMYBs) and C. baccatum (CbMYBs). Twenty tandem and forty-one segmental duplication events indicated expansion of the MYB gene family in the C. chinense genome. Five CcMYB genes i.e. CcMYB101, CcMYB46, CcMYB6, CcPHR8, CcRVE5, and two CaMYBs i.e. CaMYB3 and CaHHO1 were found within the previously reported capsaicinoid biosynthesis quantitative trait loci region. Based on phylogenetic analysis with tomato MYB proteins, the Capsicum MYBs were classified into 24 subgroups supported by conserved amino acid motifs and gene structures. Also, a total of 241 CcMYBs were homologous with 225 C. annuum, 213 C. baccatum, 125 potato,79 tomato and 23 Arabidopsis MYBs. Synteny analysis showed all 251 CcMYBs were collinear with C. annuum, C. baccatum, tomato, potato and Arabidopsis MYBs spanning over 717 conserved syntenic segments. Using transcriptome data from three fruit developmental stages, a total of 54 CcMYBs and 81 CaMYBs showed significant differential expression patterns. Further, the expression of 24 CcMYBs from transcriptome data was validated using quantitative real-time (qRT) PCR analysis. Eight out of 24 CcMYBs validated using qRT-PCR were highly expressed in fiery hot C. chinense than the low pungent C. annuum. Furthermore, the co-expression analysis revealed several MYB genes clustered with genes from capsaicinoid, anthocyanin, phenylpropanoid, carotenoid, flavonoid pathways and related to fruit shape and size. The homology modelling of 126 R2R3 CcMYBs showed high similarity with the Arabidopsis R2R3 MYB domain template suggesting their potential functional similarity at the proteome level. Further, we have identified Simple Sequence Repeat (SSR) motifs in CcMYB genes which could be used in Capsicum breeding programs. The functional roles of identified CcMYBs could be studied further so that they can be manipulated for Capsicum trait improvement.